Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure, let's solve the equation step by step.
Given:
[tex]\[ \frac{3(8x + 24)}{12} = 9 - 3(x - 4) \][/tex]
Step 1: Simplify the left side of the equation
First, distribute the 3 inside the parentheses:
[tex]\[ 3(8x + 24) = 3 \cdot 8x + 3 \cdot 24 = 24x + 72 \][/tex]
Then, divide by 12:
[tex]\[ \frac{24x + 72}{12} = \frac{24x}{12} + \frac{72}{12} = 2x + 6 \][/tex]
So, the left side of the equation simplifies to:
[tex]\[ 2x + 6 \][/tex]
Step 2: Simplify the right side of the equation
First, distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ -3(x - 4) = -3x + 12 \][/tex]
Then add the 9:
[tex]\[ 9 - 3x + 12 = -3x + 21 \][/tex]
So, the right side of the equation simplifies to:
[tex]\[ -3x + 21 \][/tex]
Step 3: Combine the simplified expressions
Now the equation is:
[tex]\[ 2x + 6 = -3x + 21 \][/tex]
Step 4: Combine like terms
Add [tex]\(3x\)[/tex] to both sides to get all [tex]\(x\)[/tex]-terms on one side:
[tex]\[ 2x + 3x + 6 = 21 \][/tex]
[tex]\[ 5x + 6 = 21 \][/tex]
Subtract 6 from both sides to isolate the [tex]\(x\)[/tex]-term:
[tex]\[ 5x = 21 - 6 \][/tex]
[tex]\[ 5x = 15 \][/tex]
Step 5: Solve for [tex]\(x\)[/tex]
Finally, divide by 5:
[tex]\[ x = \frac{15}{5} \][/tex]
[tex]\[ x = 3 \][/tex]
So, the solution is:
[tex]\[ x = 3 \][/tex]
Given:
[tex]\[ \frac{3(8x + 24)}{12} = 9 - 3(x - 4) \][/tex]
Step 1: Simplify the left side of the equation
First, distribute the 3 inside the parentheses:
[tex]\[ 3(8x + 24) = 3 \cdot 8x + 3 \cdot 24 = 24x + 72 \][/tex]
Then, divide by 12:
[tex]\[ \frac{24x + 72}{12} = \frac{24x}{12} + \frac{72}{12} = 2x + 6 \][/tex]
So, the left side of the equation simplifies to:
[tex]\[ 2x + 6 \][/tex]
Step 2: Simplify the right side of the equation
First, distribute the [tex]\(-3\)[/tex] inside the parentheses:
[tex]\[ -3(x - 4) = -3x + 12 \][/tex]
Then add the 9:
[tex]\[ 9 - 3x + 12 = -3x + 21 \][/tex]
So, the right side of the equation simplifies to:
[tex]\[ -3x + 21 \][/tex]
Step 3: Combine the simplified expressions
Now the equation is:
[tex]\[ 2x + 6 = -3x + 21 \][/tex]
Step 4: Combine like terms
Add [tex]\(3x\)[/tex] to both sides to get all [tex]\(x\)[/tex]-terms on one side:
[tex]\[ 2x + 3x + 6 = 21 \][/tex]
[tex]\[ 5x + 6 = 21 \][/tex]
Subtract 6 from both sides to isolate the [tex]\(x\)[/tex]-term:
[tex]\[ 5x = 21 - 6 \][/tex]
[tex]\[ 5x = 15 \][/tex]
Step 5: Solve for [tex]\(x\)[/tex]
Finally, divide by 5:
[tex]\[ x = \frac{15}{5} \][/tex]
[tex]\[ x = 3 \][/tex]
So, the solution is:
[tex]\[ x = 3 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.